Measuring urban walkability index for the town centre of Petaling Jaya - Che Abdullah, Ishak; Ahmad Zaki, Zulkifli; Nasrudin, Na'asah; Omar Chong, Noraini; Mohd Nor, Marina (Academica Press Solutions, 2025)
Walkability has been introduced as one of the newest elements in supporting green neighbourhood. Various studies have been conducted to identify the built environment factors that influences people’s decision to walk. From these studies, scholars have developed walkability index to measure the walkability of a specific areas. However, most of this studies are conducted outside of Malaysia. Despite the numerous advantages of using walkability index to measure walkability of an area, the application of walkability index in Malaysia is limited and scarce. Therefore, this study attempts to develop the walkability index based on Malaysian context and test the feasibility of using this walkability index in Malaysia. The walkability index indicators were adjusted to suit the Malaysian local environment and used transportation network design, land use diversity and population density as the built environment indicators. The walkability index was tested in the urban areas of Petaling Jaya and were validated by the officers from the Transport Department of Petaling Jaya City Council. Results shown that the index is able to produce walkability results and depict areas with high and low walkability among the people. This study provided useful insights on how walkability index can assist planners and stakeholders in making informed decision in improving the built environment to promote walkability among the people.